The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9ra06042a
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature selective catalytic dehydrogenation of methylcyclohexane by surface protonics

Abstract: The methylcyclohexane (MCH)-toluene cycle is a promising liquid organic hydride system as a hydrogen carrier. Generally, MCH dehydrogenation has been conducted over Pt-supported catalysts, for which it requires temperatures higher than 623 K because of its endothermic nature. For this study, an electric field was applied to Pt/TiO 2 catalyst to promote MCH dehydrogenation at low temperatures. Selective dehydrogenation was achieved with the electric field application exceeding thermodynamic equilibrium, even at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…There are three important phenomena: (i) In-situ DRIFTS measurements to evaluate the behavior of surface adsorbents showed proton hopping on the catalyst support surface based on the Grotthuss mechanism 34,35 . (ii) Considering the "inverse" KIE theory, protons with kinetic energy collide with stable reactants and accelerate the rate-determining step of the reaction 34,37,38 . (iii) EIS measurements revealed that surface ionic conduction occurs on the catalyst support at lower temperatures 34,36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are three important phenomena: (i) In-situ DRIFTS measurements to evaluate the behavior of surface adsorbents showed proton hopping on the catalyst support surface based on the Grotthuss mechanism 34,35 . (ii) Considering the "inverse" KIE theory, protons with kinetic energy collide with stable reactants and accelerate the rate-determining step of the reaction 34,37,38 . (iii) EIS measurements revealed that surface ionic conduction occurs on the catalyst support at lower temperatures 34,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Equally interestingly, in the presence of an electric field, some reactions appear to proceed beyond thermodynamic equilibrium. This has been suggested to be due to the activation of irreversible reaction pathways 18,19,34,35,37,38,49,52 .…”
Section: Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] In addition, the active migration of H atoms promotes heterogeneous catalytic reactions. [5][6][7] In such cases, the migration of H atoms on metal oxide surfaces (proton, H + ) induced by an electric eld contributes to cleavage of the rigid bonding in the stable molecules such as N^N bonding (for NH 3 synthesis [8][9][10][11][12] ), and C-H bonding (for steam reforming of CH 4 , [13][14][15] dehydrogenation of methylcyclohexane 16,17 ). H atoms mobility and reactivity play important roles in the catalytic reactions described above.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Recently, an important role of surface protonics during heterogeneous catalytic reactions was found in an electric field under both H 2 O and H 2 atmospheres. [7][8][9][10][11][12][13][14][15][16][17][18][19] It promotes low-temperature catalysis for hydrogen production, ammonia synthesis, and other processes. Electrochemical impedance spectroscopy (EIS) of oxide surfaces under a H 2 O atmosphere has been investigated to elucidate the correlation between catalysis in an electric field and surface protonics (Scheme 1).…”
mentioning
confidence: 99%